The effect of spiral trajectory correction on pseudo-continuous arterial spin labeling with high-performance gradients on a compact 3T scanner - Daehun Kang (2020)
© 2019 International Society for Magnetic Resonance in Medicine Purpose: To demonstrate the feasibility of pseudo-continuous arterial-spin–labeled (pCASL) imaging with 3D fast-spin-echo stack-of-spirals on a compact 3T scanner (C3T), to perform trajectory correction for eddy-current–induced deviations in the spiral readout of pCASL imaging, and to assess the correction effect on perfusion-related images with high-performance gradients (80 mT/m, 700T/m/s) of the C3T. Methods: To track eddy-current–induced artifacts with Archimedean spiral readout, the spiral readout in pCASL imaging was performed with 5 different peak gradient slew rate (Smax) values ranging from 70 to 500 T/m/s. The trajectory for each Smax was measured using a dynamic field camera and applied in a density-compensated gridding image reconstruction in addition to the nominal trajectory. The effect of the trajectory correction was assessed with perfusion-weighted (ΔM) images and proton-density–weighted images as well as cerebral blood flow (CBF) maps, obtained from 10 healthy volunteers. Results: Blurring artifact on ΔM images was mitigated by the trajectory correction. CBF values on the left and right calcarine cortices showed no significant difference after correction. Also, the signal-to-noise ratio of ΔM images improved, on average, by 7.6% after correction (P <.001). The greatest improvement of 12.1% on ΔM images was achieved with a spiral readout using Smax of 300~400 T/m/s. Conclusion: Eddy currents can cause spiral trajectory deviation, which leads to deformation of the CBF map even in cases of low value Smax. The trajectory correction for spiral-readout–based pCASL produces more reliable results for perfusion imaging. These results suggest that pCASL is feasible on C3T with high-performance gradients.